A low-alloy high-toughness zirconium alloy and a method for producing the same
Patent Information
- Application Number
- CN202411961691.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2044-12-30
AI Technical Summary
但是纯金属锆的强度较低,在长期使用中,可能产生变形甚至开裂等问题,导致植入手术失败
[0030]本发明向金属锆中添加钛、铌和铪元素,通过固溶强化来增加金属锆的强度。同时,为了避免高合金化可能导致的金属锆点蚀现象,本发明通过低合金化改性的手段,保证了每种合金元素的低添加量;并借助形变及热处理工艺,进一步优化其力学性能,使其能够更好地承受各种应力,从而为长期稳定地在人体内部发挥作用提供保障,满足生物医用领域对高性能植入材料的迫切需求。本发明制备的锆合金与金属锆及现役的医用植入锆铌合金相比(屈服强度310-400MPa,弹性模量~95GPa),具有较高的屈服强度(620-675MPa)和较低的弹性模量(85±2GPa),更有利于作为硬组织植入材料使用。
Smart Images

Figure CN119753394B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of alloy materials technology, and in particular to a low-alloy high-strength and high-toughness zirconium alloy and its preparation method. Background Technology
[0002] Against the backdrop of rapid development in modern industry and technology, the demand for high-performance alloy materials in human society's production and daily life is becoming increasingly urgent, giving rise to the research and development of titanium-zirconium-niobium alloys. Currently, alloys used clinically for orthopedic implants suffer from biocompatibility issues due to mismatches in elastic modulus with human bone and the release of harmful metal ions. To meet the needs of the orthopedic implant field, third-generation metastable β-type titanium alloys with low elastic modulus and good biocompatibility have been rapidly developed; however, the relatively low yield strength (≤600 MPa) of these alloys limits their widespread application. Therefore, there is an urgent need to develop medical metallic implant materials that combine low elastic modulus and high yield strength.
[0003] Zirconium metal possesses advantages over titanium metal, including better corrosion resistance, improved biocompatibility, and extremely low magnetic susceptibility (which avoids significant MRI artifacts affecting implant repair and refurbishment), making it a promising candidate for medical implantation. However, pure zirconium metal has relatively low strength, and over long-term use, it may deform or even crack, leading to implantation failure. Therefore, improving the strength of zirconium metal is crucial for expanding its application range. Summary of the Invention
[0004] To address the aforementioned technical problems, this invention provides a low-alloy high-strength and high-toughness zirconium alloy with both high strength and toughness and low elastic modulus, and a method for preparing the same.
[0005] In the technical solution of the present invention, low alloying is a conventional material modification method in the art, which improves performance by adding a small amount of alloying elements (the amount of each alloying element added is ≤5%) to the base metal.
[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0007] On one hand, the present invention provides a method for preparing a low-alloy high-strength and high-toughness zirconium alloy, comprising the following steps:
[0008] Step (1) Alloy smelting;
[0009] Step (2) Alloy homogenization;
[0010] Step (3) Hot rolling treatment: The temperature of the hot rolling treatment is 880-920℃; the reduction rate of the hot rolling treatment is 80%-85%;
[0011] Step (4) Annealing;
[0012] The alloying elements added to the low-alloy high-strength and high-toughness zirconium alloy include titanium, niobium, and hafnium.
[0013] As a preferred embodiment, the chemical composition of the low-alloy high-strength and high-toughness zirconium alloy, by mass percentage, includes: titanium: 4.8% to 5.0%; niobium: 0.5% to 5.0%; hafnium: 1.5% to 3.0%; with the balance being zirconium and unavoidable impurity elements.
[0014] In some specific implementations, step (1) uses a water-cooled copper crucible non-consumable vacuum arc furnace for alloy melting; the alloy melting is carried out in an inert atmosphere; to ensure the uniformity of the alloy ingot obtained by melting, the melting is repeated 6 to 8 times, and magnetic stirring is turned on to assist in homogenization; after the alloy melting is completed, it is cooled by circulating cooling water.
[0015] In a preferred embodiment, in step (2), the temperature for homogenizing the alloy is 880–920°C;
[0016] Preferably, the homogenization time of the alloy is 8 to 10 hours;
[0017] Preferably, the heating rate for homogenizing the alloy is 10–15 °C / min;
[0018] Preferably, the alloy homogenization process further includes a water-cooling quenching step;
[0019] Preferably, the alloy homogenization is carried out in an inert atmosphere.
[0020] In a preferred embodiment, in step (3), the hot rolling process is performed in 8 to 10 passes; the reduction rate per pass is 8% to 10%.
[0021] Preferably, a heat preservation treatment is performed before each rolling pass in the hot rolling process;
[0022] Preferably, the temperature of the heat preservation treatment is the same as the temperature of the hot rolling treatment;
[0023] Preferably, in the hot rolling process, the holding time before the first rolling pass is 25-35 minutes; the holding time before the remaining rolling passes is 2-4 minutes. In the technical solution of the present invention, the 25-35 minute holding treatment before the first rolling pass can prevent the alloy from cracking during rolling at low temperatures, and also helps to obtain a precise hot rolling temperature.
[0024] Preferably, the hot rolling process further includes a water cooling operation.
[0025] In a preferred embodiment, in step (4), the annealing temperature is 650–750°C;
[0026] Preferably, the annealing time is 10-15 minutes;
[0027] In some specific embodiments, the annealing process further includes a cooling operation; the cooling is carried out in the furnace to 250-350°C and then air-cooled.
[0028] On the other hand, the present invention provides a low-alloy high-strength and high-toughness zirconium alloy obtained by the above preparation method.
[0029] This invention has the following advantages and beneficial effects:
[0030] This invention adds titanium, niobium, and hafnium to metallic zirconium to increase its strength through solid solution strengthening. Simultaneously, to avoid pitting corrosion that may occur with high alloying, this invention employs low-alloying modification to ensure low addition levels of each alloying element. Furthermore, by utilizing deformation and heat treatment processes, its mechanical properties are further optimized, enabling it to better withstand various stresses. This ensures long-term stable function within the human body, meeting the urgent need for high-performance implant materials in the biomedical field. Compared to metallic zirconium and existing medical implant zirconium-niobium alloys (yield strength 310-400 MPa, elastic modulus ~95 GPa), the zirconium alloy prepared by this invention exhibits a higher yield strength (620-675 MPa) and a lower elastic modulus (85±2 GPa), making it more suitable for use as a hard tissue implant material.
[0031] Furthermore, the preparation method provided by this invention is simple and suitable for industrial production. Attached Figure Description
[0032] Figure 1 This is a schematic diagram of the sample shape and size in the tensile test experiment of low alloy zirconium-titanium-niobium hafnium alloy in an embodiment of the present invention.
[0033] Figure 2 This is an XRD test image of the low-alloy zirconium-titanium-niobium-zirconium alloy in an embodiment of the present invention.
[0034] Figures 3a-3c These are microstructure diagrams of the low-alloy zirconium-titanium-niobium-zirconium alloys in Examples 1 to 3 of this invention.
[0035] Figure 4 These are the mechanical property test results of the low-alloy zirconium-titanium-niobium-zirconium alloy in the embodiments of the present invention. Detailed Implementation
[0036] The following embodiments are merely some, not all, of the embodiments of the present invention. Therefore, the detailed descriptions of the embodiments provided below are not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0037] In this invention, unless otherwise specified, all equipment and raw materials are commercially available or commonly used in the industry. The methods described in the following embodiments are conventional methods in the art, unless otherwise specified.
[0038] Example 1
[0039] The preparation process of the low-alloy zirconium-titanium-niobium hafnium alloy in this embodiment is as follows:
[0040] Industrial pure zirconium, pure titanium, and pure niobium were smelted in an argon atmosphere using a water-cooled copper crucible non-consumable vacuum arc furnace. The ingots were repeatedly smelted and cast seven times while magnetic stirring was activated to obtain zirconium-titanium-niobium-hafnium alloy ingots.
[0041] The alloy ingot was placed in a vacuum tube furnace and heated to 900℃ at a heating rate of 15℃ / min for 10 hours to homogenize. Argon gas was continuously introduced during the homogenization process, followed by water quenching.
[0042] The muffle furnace was heated to 900°C at a heating rate of 10°C / min. The homogenized alloy ingot was placed in the muffle furnace and held at that temperature for 30 minutes. After holding, it was immediately removed and hot-rolled on a twin-roll mill at 900°C. Ten passes were used for the hot rolling, with a reduction of 8.2% per pass. After the first pass, the ingot was held at 900°C in the muffle furnace for 5 minutes before each subsequent pass. The final deformation was approximately 82%. The ingot was then water-cooled to room temperature.
[0043] The rolled sheet was annealed at 700°C for 10 minutes in an argon atmosphere in a tube furnace; after annealing, it was cooled to 300°C in the furnace and then air-cooled; finally, the surface oxide layer was polished clean and washed to obtain a low-alloy zirconium-titanium-niobium hafnium alloy sheet.
[0044] The thickness of the low-alloy zirconium-titanium-niobium hafnium alloy plate prepared in this embodiment is 2.5 mm.
[0045] The low-alloy zirconium-titanium-niobium-hafnium alloy plate prepared in this embodiment has the following composition: Zr-4.91Ti-0.94Nb-2.35Hf.
[0046] Example 2
[0047] The preparation process of the low-alloy zirconium-titanium-niobium hafnium alloy in this embodiment is as follows:
[0048] Industrial pure zirconium, pure titanium, and pure niobium were smelted in an argon atmosphere using a water-cooled copper crucible non-consumable vacuum arc furnace. The ingots were repeatedly smelted and cast seven times while magnetic stirring was activated to obtain zirconium-titanium-niobium-hafnium alloy ingots.
[0049] The alloy ingot was placed in a vacuum tube furnace and heated to 900℃ at a heating rate of 15℃ / min for 10 hours to homogenize. Argon gas was continuously introduced during the homogenization process, followed by water quenching.
[0050] The muffle furnace was heated to 900°C at a heating rate of 10°C / min. The homogenized alloy ingot was placed in the muffle furnace and held for 30 minutes. After holding, it was immediately removed and hot-rolled on a twin-roll mill at 900°C. Ten passes were used for rolling, with a reduction of 8.5% in each pass. After the first pass, the ingot was held at 900°C in the muffle furnace for 5 minutes before each subsequent pass. The final deformation was approximately 85%. The ingot was then water-cooled to room temperature.
[0051] The rolled sheet was annealed at 700°C for 10 minutes in an argon atmosphere in a tube furnace; after annealing, it was cooled to 300°C in the furnace and then air-cooled; finally, the surface oxide layer was polished clean and washed to obtain a low-alloy zirconium-titanium-niobium hafnium alloy sheet.
[0052] The thickness of the low-alloy zirconium-titanium-niobium hafnium alloy plate prepared in this embodiment is 2.5 mm.
[0053] The low-alloy zirconium-titanium-niobium-hafnium alloy plate prepared in this embodiment has the following composition: Zr-4.87Ti-2.50Nb-2.21Hf.
[0054] Example 3
[0055] The preparation process of the low-alloy zirconium-titanium-niobium hafnium alloy in this embodiment is as follows:
[0056] Industrial pure zirconium, pure titanium, and pure niobium were smelted in an argon atmosphere using a water-cooled copper crucible non-consumable vacuum arc furnace. The ingots were repeatedly smelted and cast seven times while magnetic stirring was activated to obtain zirconium-titanium-niobium-hafnium alloy ingots.
[0057] The alloy ingot was placed in a vacuum tube furnace and heated to 900℃ at a heating rate of 15℃ / min for 10 hours to homogenize. Argon gas was continuously introduced during the homogenization process, followed by water quenching.
[0058] The muffle furnace was heated to 900°C at a heating rate of 10°C / min. The homogenized alloy ingot was placed in the muffle furnace and held for 30 minutes. After holding, it was immediately removed and hot-rolled on a two-roll mill at 900°C. Ten passes were used for rolling, with a reduction of 8.4% per pass. After the first pass, the ingot was held at 900°C in the muffle furnace for 5 minutes before each subsequent pass. The final deformation was approximately 84%. The ingot was then water-cooled to room temperature.
[0059] The rolled sheet was annealed at 700°C for 10 minutes in an argon atmosphere in a tube furnace; after annealing, it was cooled to 300°C in the furnace and then air-cooled; finally, the surface oxide layer was polished and cleaned to obtain a low-alloy zirconium-titanium-niobium hafnium alloy sheet.
[0060] The thickness of the low-alloy zirconium-titanium-niobium hafnium alloy plate prepared in this embodiment is 2.5 mm.
[0061] The low-alloy zirconium-titanium-niobium-hafnium alloy plate prepared in this embodiment has the following composition: Zr-4.95Ti-4.93Nb-2.25Hf.
[0062] Performance testing:
[0063] The phase composition of the low-alloy zirconium-titanium-niobium hafnium alloy plates prepared in the above examples was tested using X-ray diffraction (XRD), and the results are shown in [Figure number missing]. Figure 2 ,from Figure 2 As can be seen, the addition of Nb can change the phase composition of the Ti-Zr alloy, thus affecting the alloy's β-stabilization ability. With further increases in Nb content, XRD results show that the alloy in Example 1 contains an α phase, the alloy in Example 2 contains both α and β phases, and the alloy in Example 3 contains α, β, and ω phases. The alloying element Ti has a neutral effect on the phase stability of metallic zirconium when no other β-stabilizing elements are present. When other β-stabilizing elements are present, its β-stabilization ability increases with increasing content, which can improve the strength and toughness of the material. At the same time, the ω phase can improve the strength of the material while reducing its magnetic susceptibility.
[0064] The microstructure of the low-alloy zirconium-titanium-niobium alloy plates prepared in the above examples was observed using scanning electron microscopy (SEM), and the test results are shown in Figure 3. Figure 3 shows that the microstructure of the alloy in Example 1 is characterized by fine, short rod-shaped grains (thickness less than 1 μm, length 3–5 μm) and a very small amount of intergranular β phase. The microstructures of Examples 2 and 3 are similar, exhibiting typical incomplete recrystallization, consisting mainly of fine equiaxed crystals (size 0.5–1 μm) and a small amount of short rod-shaped grains (thickness approximately 0.7–1 μm, length 2–3 μm), along with a large amount of β phase matrix.
[0065] Tensile tests were conducted on the low-alloy zirconium-titanium-niobium hafnium alloy plates prepared in Examples 1-3, as follows: The plates were cut using wire cutting... Figure 1 For the tensile specimens shown, at least five tensile specimens were cut from each sample, and the surfaces were polished smooth. The mechanical properties were tested using a uniaxial tensile test at room temperature. During the test, the tensile displacement of the specimens was monitored throughout using an extensometer. Strain control was employed during tensile testing at a rate of 5 × 10⁻⁶. -4 s -1 The test results are shown below. Figure 4 And as shown in Table 1. From Figure 4 As can be seen from Table 1, the prepared material has the properties of high yield strength (620-700 MPa) and low Young's modulus (85±2 GPa).
[0066] Table 1
[0067] Example 1 83.5±0.5 623.8±10.0 737.3±7.1 11.1±1.5 Example 2 86.5±0.5 653.5±20.1 766.6±14.0 11.0±3.0 Example 3 85±2 675.1±19.0 746.1±42.1 7.3±3.2
[0068] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a low-alloy high-strength and high-toughness zirconium alloy, characterized in that, Includes the following steps: Step (1) Alloy smelting; Step (2) Alloy homogenization; Step (3) Hot rolling treatment: The temperature of the hot rolling treatment is 880~920℃; the reduction rate of the hot rolling treatment is 80%~85%; Step (4) Annealing; The alloying elements added to the low-alloy high-strength and high-toughness zirconium alloy include titanium, niobium, and hafnium; the chemical composition of the low-alloy high-strength and high-toughness zirconium alloy, by mass percentage, includes: titanium: 4.8%~4.95%; niobium: 0.5%~5.0%; hafnium: 1.5%~3.0%; the balance being zirconium and unavoidable impurity elements; In step (4), the annealing temperature is 650~750℃.
2. The preparation method according to claim 1, characterized in that, Step (1) The alloy is smelted using a water-cooled copper crucible non-consumable vacuum electric arc furnace; the alloy smelting is carried out in an inert atmosphere; the smelting is repeated 6 to 8 times and magnetic stirring is turned on; after the alloy smelting is completed, it is cooled by circulating cooling water.
3. The preparation method according to claim 1, characterized in that, In step (2), the temperature for homogenizing the alloy is 880~920℃. The homogenization time for the alloy is 8-10 h; The heating rate for homogenizing the alloy is 10~15℃ / min.
4. The preparation method according to claim 1, characterized in that, In step (2), the alloy homogenization process further includes a water-cooling quenching step; The alloy homogenization is carried out in an inert atmosphere.
5. The preparation method according to claim 1, characterized in that, In step (3), the hot rolling process is performed in 8 to 10 passes; the reduction rate per pass is 8% to 10%.
6. The preparation method according to claim 5, characterized in that, The hot rolling process also includes a heat preservation treatment before each rolling pass. The temperature of the heat preservation treatment is the same as the temperature of the hot rolling treatment. In the hot rolling process, the holding time before the first rolling pass is 25-35 min; the holding time before the remaining rolling passes is 2-4 min. The hot rolling process also includes a water cooling operation.
7. The preparation method according to claim 1, characterized in that, In step (4), the annealing time is 10~15 min.
8. The preparation method according to claim 1, characterized in that, In step (4), the annealing process also includes a cooling operation; The cooling process involves cooling the furnace to 250-350°C and then air cooling.
Citation Information
Patent Citations
High-strength corrosion-resistant weldable aluminum-magnesium-erbium-zirconium alloy wide sheet and preparation method thereof
CN111850361A
High-strength zirconium alloy and preparation method thereof
CN113186425A